Pengaruh Pemberian Ekstrak Etanol Daun Kunyit (Curcuma Domestica Val) Terhadap Kadar Glukosa Darah Tikus Putih (Rattus Norvegicus) Jantan Yang Di Induksi - Akmalul Habib Damanik; Asyrun Alkhairi Lubis; Ermi Girsang (STIKes Ibnu Sina Ajibarang, 2024)
Indonesia is the largest archipelago in the world (17,504 islands). In addition, Indonesia has abundant natural resources and fertile soil that allows a wide variety of plants to live. Curcuma domestica val, known as turmeric, is one of Indonesia's medicinal plants. A number of active ingredients found in turmeric have been shown in studies to have potential health benefits, including anti-diabetic anti-inflammatory, anti-cancer, cough medicine, liver medicine, and Alzheimer's disease. Based on the results of phytochemical research, flavonoids, alkaloids, tannins, triterpenoids, steroids, saponins, and glycosides are present in the ethyl ethanol extract of turmeric leaves (Curcuma domestica Val). Diabetes mellitus is a metabolic condition characterised by increased blood glucose levels caused by disruption of the insulin hormone which functions to lower blood glucose levels to maintain body homeostasis. Because of the close relationship between diabetes mellitus and lifestyle, diet, sleep, work, daily routine activities and others must be balanced. This study was conducted in the laboratory and was experimental in nature using male white rats as research subjects. Rats were induced using Alloxan at a dose of 100 mg/kgBB. Rats were divided into 6 groups, each consisting of 5 rats. Group 1 is a normal group, Group 2 is a negative group only given aquadest and induced with Alloxan.